Mapping brain structure and function in professional fencers: A model to study training effects on central nervous system plasticity - Cordani, Claudio; Preziosa, Paolo; Gatti, Roberto; Castellani, Carlotta; Filippi, Massimo; Rocca, Maria Assunta (Human brain mapping, 2022)
Brain magnetic resonance imaging (MRI) studies have shown different patterns of structural and functional reorganization in high‐level athletes compared with controls, but little is known about their relationship with interlimb coordination mechanisms. To this aim, we investigated brain structural and functional differences in high‐level fencers compared with nonathlete controls and the MRI substrates of interlimb coordination in elite athletes. Fourteen right‐handed male fencers (median age = 22.3 years) and 15 right‐handed age‐ and sex‐matched healthy subjects (median age = 22.4 years) underwent structural and functional MRI acquisition during the execution of cyclic bimanual‐movements as well as during in‐phase and antiphase hand/foot‐movements of the dominant‐right limbs. No between‐group differences were found in gray matter volumes and white matter architecture. Active‐fMRI showed that controls versus fencers had higher activations in parietal and temporal areas during bimanual‐task; whereas fencers versus controls had higher activations in the basal ganglia. During in‐phase task, controls versus fencers showed higher activation of right cerebellum, whereas fencers had higher activity mainly in frontal areas. The functional‐connectivity (FC) analysis showed that fencers versus controls had an increased FC between left motor cortex and fronto‐temporal areas as well as bilateral thalami during the different tasks. Intensive and prolonged fencing activity is associated with brain functional changes mainly involving frontal regions related to high‐level motor control and planning of complex tasks. These modifications are likely to reflect an optimization of brain networks involved in motor activities, including interlimb coordination tasks, occurring after intensive training. Intensive and prolonged fencing activity is associated with brain functional changes mainly involving frontal regions related to high‐level motor control and planning of complex tasks. These modifications are likely to reflect an optimization of brain networks involved in motor activities, including interlimb coordination tasks, occurring after intensive training.